Mewujudkan Desa Maju Reforma Agraria - Nurdin, Iwan (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
Abstract :Law Nr.6/2014 on Village has brought expectations of the opportunities of the villages to manage their natural resources independently with the support of Village Fund Allocation (Alokasi Dana Desa – ADD) from central government. Nonetheless, it is commonly known that village’s natural resources have long been monopolied and dominated by non villagers. This condition caused agrarian cryses in village area. Joko Widodo regime has the plan to set up land redistribution program for 9 millions hectares of land and 12.7 millions hectares of social forestry. These two types of land redistribution are called as Agrarian Reform Program. The combination of village development program and agrarian reform is presented as the concept of “Desa Maju Reforma Agraria - Damara” (Advance Villages Agrarian Reform) as the proposal from the civil society. Intisari: Kehadiran UU No.6/2014 tentang Desa telah membawa sejumlah harapan tentang kemungkinan adanya pengelolaan sumber daya alam di desa dilakukan secara mandiri oleh desa dengan dukungan Alokasi Dana Desa (ADD) dari Pemerintah Pusat. Namun, kita tahu bahwa sumber daya alam di desa telah lama dikuasai oleh aktor-aktor diluar desa. Hal yang mengakibatkan krisis agraria di pedesaan. Pemerintah Joko Widodo berencana menjalankan program redistribusi tanah seluas 9 juta hektar dan perhutanan sosial seluas 12,7 juta hektar. Keduanya disebut sebagai program Reforma Agraria. Kombinasi pembangunan pedesaan dan reforma agraria tersebut disajikan dalam konsep Desa Maju Reforma Agraria sebagai usulan dari masyarakat sipil.